Flat clathrin lattices are linked to metastatic potential in colorectal cancer - Charlotte Cresens; Guillermo Solís-Fernández; Astha Tiwari; Rik Nuyts; Johan Hofkens; Rodrigo Barderas; Susana Rocha (iScience, 2023)
Summary: Clathrin assembles at the cells’ plasma membrane in a multitude of clathrin-coated structures (CCSs). Among these are flat clathrin lattices (FCLs), alternative clathrin structures that have been found in specific cell types, including cancer cells. Here we show that these structures are also present in different colorectal cancer (CRC) cell lines, and that they are extremely stable with lifetimes longer than 8 h. By combining cell models representative of CRC metastasis with advanced fluorescence imaging and analysis, we discovered that the metastatic potential of CRC is associated with an aberrant membranous clathrin distribution, resulting in a higher prevalence of FCLs in cells with a higher metastatic potential. These findings suggest that clathrin organization might play an important yet unexplored role in cancer metastasis.